PRINCIPAL MANAGEMENT IN IMPROVING THE QUALITY OF EDUCATION AT FATHUL ULUM MIDDLE SCHOOL, BOARDING SCHOOL - BASED - Muhamad Hanif; Bahtiar Nur; Tica Renny Vansisca (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to 1) determine the process of implementing principal management in improving the quality of education at SMP Fathul Ulum Islamic boarding school-based junior high school, 2) identify the supporting and inhibiting factors in the principal’s management process in improving the quality of education at SMP Fathul Ulum Islamic boarding school-based junior high school, and 3) examine the principal’s management process toward improving the quality of education at SMP Fathul Ulum Islamic boarding school-based junior high school. This research employed a descriptive qualitative method using interviews, observations, and documentation as data collection techniques. The results showed that in improving the quality of education at SMP Fathul Ulum, the principal implemented programs aimed at enhancing the quality of school personnel in resource management and program planning, as well as encouraging the participation of the teacher council in supporting education at the Islamic boarding school-based SMP Fathul Ulum. In the implementation of principal management, there are supporting and inhibiting factors; therefore, appropriate solutions are needed to anticipate and overcome the inhibiting factors.